WHY DO STUDENTS FEEL TIRED EVEN AFTER SLEEPING? PSYCHOLOGICAL CAUSES OF MENTAL FATIGUE IN ADOLESCENTS - qizi, Yo’ldasheva Shahrizoda Ibrohim (Research Focus International Scientific Journal, 2026)
This study explores why students feel tired even after getting enough sleep. The research was conducted with 20 students using a questionnaire and one-week screen time observation. The results show that phone use, stress, and overthinking are the main causes of fatigue rather than lack of sleep. These findings suggest that improving sleep habits and reducing screen time can help increase students’ energy and academic performance.